Islamic economics education in Southeast Asian universities - Barom, Mohd Nizam (Centre for Islamic Economics, International Islamic University Malaysia & International Institute of Islamic Thought, 2013)
This book discusses and analyzes an area of contemporary Islamic economics and finance that is relatively under-written, i.e., Islamic Economics Education. It provides a conceptual introduction by experts in Islamic Thought and Education on the urgent need for curriculum reforms in university education that is represented by integration between Islamic heritage (al-Turath al-Islami) and modern knowledge/disciplines. In this context, the Islamization of knowledge agenda, properly understood and undertaken by qualified academics, is a legitimate process required in the teaching of economics. ‘Islamic Economics Education in Southeast Asian Universities’ presents the case studies and experiences of selected universities in Malaysia and Indonesia offering Islamic economics programs, reflects critically on these experiences, identifies important issues and challenges, and offers recommendations for the future progress of Islamic economics education.